Efektivitas Pengelolaan Arsip Digital dalam Mewujudkan Akuntabilitas Pemerintahan di Provinsi Bali - Ridwan Hapipi; Muhadam Labolo; Irfan Setiawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Digital archives are an essential instrument in realizing transparent and well-administered government accountability. This study analyzes the effectiveness of digital archive management in realizing government accountability in Bali Province, identifies its supporting and inhibiting factors, and formulates a follow-up plan. It employs Tangkilisan's (2005) effectiveness theory, comprising four dimensions: target achievement, adaptability, job satisfaction, and responsibility. A descriptive qualitative approach was applied, with data collected through in-depth interviews, observation, and documentation involving nine informants from the Bali Provincial Government and the National Archives of the Republic of Indonesia, analyzed using NVivo software and validated through triangulation. The results show that digital archive management in Bali Province has been implemented with positive progress, particularly through the Kantor Virtual application and the National Archives Information Network (JIKN), yet it is not fully optimal, especially in archive media conversion, collection completeness, and legal certainty. The main supporting factors are leadership and budget support, while the inhibiting factors are limited human resources and archivist competence, inadequate facilities and information technology infrastructure, and the absence of comprehensive regulations and standard operating procedures. The study recommends strengthening human resource capacity, standardizing facilities, and establishing a regional legal framework as gradual follow-up measures accompanied by monitoring and evaluation.